Volumetric response of intracranial meningioma after photon or particle irradiation - Mozes, Petra; Tonndorf-Martini, Eric; Dittmar, Anne; Debus, Jürgen (Acta oncologica, 2017)
Background: Meningiomas are usually slow growing, well circumscribed intracranial tumors. In symptom-free cases observation with close follow-up imaging could be performed. Symptomatic meningiomas could be surgically removed and/or treated with radiotherapy. The study aimed to evaluate the volumetric response of intracranial meningiomas at different time points after photon, proton, and a mixed photon and carbon ion boost irradiation.Patients and methods: In Group A 38 patients received proton therapy (median dose: 56 GyE in 1.8-2 GyE daily fractions) or a mixed photon/carbon ion therapy (50 Gy in 2 Gy daily fractions with intensity modulated radiotherapy (IMRT) and 18 GyE in 3 GyE daily dose carbon ion boost). Thirty-nine patients (Group B) were treated by photon therapy with IMRT or fractionated stereotactic radiotherapy technique (median dose: 56 Gy in 1.8-2 Gy daily fractions). The delineation of the tumor volume was based on the initial, one- and two-year follow-up magnetic resonance imaging and these volumes were compared to evaluate the volumetric tumor response.Results: Significant tumor volume shrinkage was detected at one- and at two-year follow-up both after irradiation by particles and by photons. No significant difference in tumor volume change was observed between photon, proton or combined photon plus carbon ion boost treated patients. WHO grade and gender appear to be determining factors for tumor volume shrinkage.Conclusion: Significant volumetric shrinkage of meningiomas could be observed independently of the applied radiation modality. Long-term follow-up is recommended to evaluate further dynamic of size reduction and its correlation with outcome data.
Published online: 02 Dec 2016
Gesehen am 23.05.2018